Microbiome affects mice metabolic homeostasis via differential regulation of gene expression in the brain and gut - Wynne Milhouse; Anna Clapp Organski; Xun Sun; Derek Ai; Baohua Zhou; Tzu‐Wen L. Cross; Hongxia Ren (Physiological Reports)
Abstract The gut microbiome (GMB) regulates digestion, metabolism, immunity, and energy homeostasis. This study investigates how gut microbiota integrate the regulation in the neuroendocrine and enteroendocrine systems, with a focus on G protein‐coupled receptors (GPCRs) in the brain‐gut axis and sex differences. Germ‐free (GF) mice exhibited increased hypothalamic expression of the anorexigenic neuropeptide and decreased expression of the negative regulator of leptin signaling. GF males had significantly lower serum leptin levels compared to conventional (CON) males, highlighting a potential link between the microbiome and leptin resistance. In the gut, GF mice demonstrated heightened expression of anorexigenic gut hormones, including peptide YY (Pyy) and cholecystokinin (Cck), in addition to increased levels of G protein‐coupled receptors (GPCRs) involved in gut hormone secretion and nutrient metabolism, particularly in females. While carbohydrate metabolism genes were upregulated in CON mice, lipid metabolism genes were predominantly higher in GF mice. These findings suggest that the gut microbiota downregulates genes involved in appetite suppression, modulates GPCRs linked to gut hormone secretion, and contributes to leptin resistance, particularly in males. This research underscores the importance of the gut microbiome in host metabolism and reveals potential molecular targets for novel treatments of metabolic diseases.